2000
DOI: 10.1097/00001756-200009280-00008
|View full text |Cite
|
Sign up to set email alerts
|

Systemic nitroglycerin increases nNOS levels in rat trigeminal nucleus caudalis

Abstract: Systemic administration of nitroglycerin, a nitric oxide donor, triggers in migraineurs a delayed attack of unknown mechanisms. Subcutaneous nitroglycerin (10 mg/kg) produced a significant increase of nitric oxide synthase (NOS)- and c-fos-immunoreactive neurons in the cervical part of trigeminal nucleus caudalis in rats after 4 h. This effect was not observed in the thoracic dorsal horn. Similar increase of NOS and c-fos was obtained in the brain stem after a somatic nociceptive stimulus, i.e. on the side of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
94
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 11 publications
11
94
2
Order By: Relevance
“…It is also well-known, that NTG-a nitric oxide donor (NO)-can initiate trigeminal activation and sensitization in animals as well (Pardutz et al, 2000;Tassorelli and Joseph, 1995). In rats, it has been shown that NTG produced an increase in the area covered by 5-HT-immunoreactive fibres (Pardutz et al, 2002), which suggests that NO influences the 5-HT system.…”
Section: Introductionmentioning
confidence: 99%
“…It is also well-known, that NTG-a nitric oxide donor (NO)-can initiate trigeminal activation and sensitization in animals as well (Pardutz et al, 2000;Tassorelli and Joseph, 1995). In rats, it has been shown that NTG produced an increase in the area covered by 5-HT-immunoreactive fibres (Pardutz et al, 2002), which suggests that NO influences the 5-HT system.…”
Section: Introductionmentioning
confidence: 99%
“…c-fos, CGRP [98,136], nNOS-immunoreactivity in the NTG model [89], and c-fos [137], nNOS [111], CGRP alterations [110] following the ES of the TRG.…”
Section: Electrical Stimulation Of the Tsmentioning
confidence: 92%
“…It is abundant in the superficial layers of the dorsal horn of the spinal cord [89][90][91]. The inhibition of NOS was showed to be able to ameliorate the symptoms of spontaneous migraine attacks [92].…”
Section: Chemical Stimulation Of the Tsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increase in neuronal NOS-(nNOS) and CaMKIIα-IR neurones in the C1-C2 were detected four hours after systemic administration of NTG in male rats, suggesting the presence of selfamplifying mechanisms in this area, possibly linked to a central sensitization process (Pardutz et al, 2000;. The changes observed in expression of sensitization markers were attenuated by lysine acetylsalicylate and by NS398 (selective cyclooxygenase-2 inhibitor) (Pardutz et al, 2004;Varga et al, 2007;.…”
Section: Nitroglycerin Model Of Migraine Headachementioning
confidence: 97%